1994
DOI: 10.1111/j.1348-0421.1994.tb02143.x
|View full text |Cite
|
Sign up to set email alerts
|

Growth Medium Containing Cyclodextrin and Low Concentration of Horse Serum for Cultivation of Helicobacter pylori

Abstract: Abstract:The

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

1995
1995
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 13 publications
1
11
0
Order By: Relevance
“…As in our study, several other groups have reported growth enhancement of H. pylori when culture medium is supplemented with ␤-cyclodextrin (10,16,22,24). However, it appears that not all preparations of ␤-cyclodextrins are able to support H. pylori growth (8,16), perhaps explaining why one group was unable to obtain growth of H. pylori in media supplemented with ␤-cyclodextrin (30).…”
Section: Discussionsupporting
confidence: 65%
“…As in our study, several other groups have reported growth enhancement of H. pylori when culture medium is supplemented with ␤-cyclodextrin (10,16,22,24). However, it appears that not all preparations of ␤-cyclodextrins are able to support H. pylori growth (8,16), perhaps explaining why one group was unable to obtain growth of H. pylori in media supplemented with ␤-cyclodextrin (30).…”
Section: Discussionsupporting
confidence: 65%
“…Other bacterially mediated autoimmune diseases in which persistent infection and induction of autoimmune pathology have been postulated to contribute to disease pathology include gastric inflammation (Helicobacter pylori) (4,44) and arteriosclerosis (Chlamydia pneumoniae) (22,36). In the former case, the organism is clearly implicated, since the disease responds to elimination of the organism, whereas in the latter case, the organism may either contribute to the pathogenesis of the atherosclerotic plaque or merely act as a colonizer of the diseased and compromised tissue.…”
Section: Discussionmentioning
confidence: 99%
“…In an effort to overcome some of these problems, various studies have described the use of chemically defined compounds belonging to the CD group as substitutes for serum in both solid and liquid media [6,7,15,21]. CDs are cyclic oligosaccharides that are thought to reduce the effective free concentration of toxic substrates and ⁄ or products to levels that are not inhibitory to microorganisms (reviewed in [32]).…”
Section: Discussionmentioning
confidence: 99%